2011
DOI: 10.1007/s10753-011-9357-x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Expression of β1,4-Galactosyltransferase-I in Cartilage and Synovial Tissue of Patients with Osteoarthritis

Abstract: Osteoarthritis (OA) is considered a complex illness, characterized by cartilage degeneration, secondary synovial membrane inflammation, and subchondral bone sclerosis. Previous studies have shown β1,4-galactosylransferase-I (β1,4-GalT-I) to be a key inflammatory mediator that participates in the initiation and maintenance of inflammatory reaction in diseases. In the present study, we investigated the expression and possible biological function of β1,4-GalT-I in the cartilage and synovial tissue of OA patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
1
6
1
Order By: Relevance
“…Numerous studies have confirmed that B4GALT1 has a key role in inflammatory processes associated with numerous diseases, including OA and rheumatic arthritis (RA). A previous study indicated that the expression of B4GALT1 was induced in the cartilage and synovial tissue of OA patients when compared with healthy controls and may be an important a key inflammatory mediator in OA (36). By contrast, the expression of B4GALT1 was identified to be downregulated in OA samples in the present study.…”
Section: Discussioncontrasting
confidence: 65%
“…Numerous studies have confirmed that B4GALT1 has a key role in inflammatory processes associated with numerous diseases, including OA and rheumatic arthritis (RA). A previous study indicated that the expression of B4GALT1 was induced in the cartilage and synovial tissue of OA patients when compared with healthy controls and may be an important a key inflammatory mediator in OA (36). By contrast, the expression of B4GALT1 was identified to be downregulated in OA samples in the present study.…”
Section: Discussioncontrasting
confidence: 65%
“…The two isoforms are type II membrane-bound glycoproteins and reside in Golgi apparatus and a portion of the longer protein functions on the cell surface as a recognition molecule by binding with appropriate glycoside substrates (5). Consequently, the B4GALT1 plays important roles in numerous physiological and pathological processes such as inflammation, sperm-egg interaction, embryogenesis, and morphogenesis, development of the central nervous system, cell migration, cancer progression and metastasis (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Although considered mainly as a housekeeping gene, a large number of studies have shown a differential expression of B4GALT1 in mammary gland, brain and other normal tissues such as the cartilage (7,9,10). On the other hand, this gene has been highly implicated in oncogenesis and tumor progression (6,(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…One of them, β1,4-GalT I, catalyzes attachment of β1,4-galactose to GlcNAc residue, which is absent in plants and fungi3066. In humans, this enzyme is encoded by ENSG000000860626768. The peptide sequence of this enzyme contains 2 Pfam domains (Domain IDs: PF13733 and PF02709).…”
Section: Resultsmentioning
confidence: 99%